Subgenomic RNAs mediate expression of cistrons located internally on the genomic RNA of tobacco necrosis virus strain A. - Meulewaeter, F (1992)
Upon infection of tobacco protoplasts, the genomic RNA of tobacco necrosis virus strain A (TNV-A) accumulates linearly in time. The accumulation patterns of the two subgenomic RNAs resemble those of endogenous mRNAs in that the peak levels are reached after several hours. The accumulation of the 1.3-kb subgenomic RNA is delayed by 1 h compared with that of the 1.6-kb subgenomic RNA, which illustrates the important role of the subgenomic RNAs in the regulation of TNV-A gene expression. The locations of the 5' nucleotides of the subgenomic RNAs reveal that the 5'-proximal cistrons of the 1.6- and 1.3-kb RNAs encode an 8-kDa protein from open reading frame (ORF) 3 and the coat protein from ORF 5, respectively. In a wheat germ translation system, a synthetic transcript resembling the 1.6-kb RNA expresses both ORFs 3 and 4. Moreover, the synthesis of the 6-kDa protein from ORF 4 depends on the translation efficiency of ORF 3, suggesting that in vivo, ORFs 3 and 4 are both expressed from the 1.6-kb RNA. The major in vitro translation product of TNV-A genomic RNA is the coat protein. We show that the region upstream of the coat protein promotes internal initiation of translation in vitro. However, this region is functionally inactive in vivo, suggesting that TNV-A genomic RNA is not important for coat protein synthesis in plants.